Sustainable Utilization of Dredged Sediment from Air Putih Ferry Port: Economic and Environmental Analysis for Transportation Infrastructure Development - Schouten, Femmy; Kabuhung, Gilbert Matthew D’Angelo; Sembodo, Agus; Sejati, Dian Virda; Aprilia, Nyimas Arnita; Martin, Made Happy (IWJ : Inland Waterways Journal, 2025)
Sediment dredging at the Water Putih Crossing Port (1.4675° N, 102.1167° E) produced 68,400 m³ of material (60% mud, 30% sand, 10% gravel) that could potentially be utilized for sustainable transportation infrastructure. This study analyzes material characteristics, economic feasibility, and environmental impact through a mixed approach (quantitative and qualitative). Laboratory test results show that sand and gravel meet the standards of road construction materials (CBR 25-45%), while mud (CBR 3%) requires stabilization. A Life Cycle Assessment (LCA) analysis revealed that the use of sediment as a road material generates an income of USD 20/m³ with the lowest carbon emissions (5.2 kg CO₂/m³), compared to coastal reclamation (4.8 kg CO₂/m³) or waste disposal (12.3 kg CO₂/m³). The study emphasizes the importance of substituting cement with geopolymers to reduce emissions by up to 40% as well as the development of a green logistics model. These findings form the basis for policy recommendations for sustainable sediment management, supporting the circular economy and the Sustainable Development Goals (SDGs) targets in the infrastructure sector.